Equality as a principle of justice: Philosophical reflections in the globalization era - Höffe, Otfried (Estudios de Filosofía, 2008)
The next article defends the thesis of an existing globalizing concept of justice despite the cultural differences. This concept is based on equality, looking for the establishment of a democratic global juridical order that guarantees justice administration inside and between States. The article offers a conceptual ground about the possibility of such order to be and also about the tasks and challenges that are founded in its pretention to establish some social and environmental protection criteria that look for the start of a global development policy.